Penerapan Green Architecture Pada Perancangan Gedung MICE (Meeting, Incentive, Convention, Exhibition) Di Kota Kendari - Dian Puteri Nurbaity; Jaka Surya Suwandi; Ilham Ilham (Arsitektur Universitas Muhammadiyah Kendari, 2022)
Kendari City is one of the cities in Indonesia that is experiencing a fairly rapid industrial development. This development is marked by the existence of frequent business activities such as meetings, conferences, seminars, exhibitions and other activities, both formal and informal. These various activities need solutions and wise steps by the Government to provide a forum that can accommodate business opportunities for regional economic growth, especially in the service sector. Because so far, various activities have been held in places that provide limited facilities, such as hotels, sports halls, and the ex-MTQ area. Therefore, the City of Kendari needs to provide MICE Building facilities (meetings, incentives, conventions, exhibitions) that are able to accommodate these activities with various independent facilities and are not tied to other functions or merely as a complement to functions in a building such as hotels and others. In planning, this research uses a quantitative descriptive approach. In addition, in processing the location and site, the MICE Building is planned to be located in Poasia District, Kendari City. The building that carries the theme of Green Architecture is expected to provide solutions in energy efficiency efforts in buildings and become one of the presentative means that answer the needs of the community, especially business people in Kendari City.